STRATEGI MAJELIS TAKLIM TERHADAP PENGEMBANGAN DAKWAH - St. Aisyah BM (Jurnal Berita Sosial, 2018)
In general, Islamic education is directed in attempt to guide and develop the potential of human nature that he can portray himself as a servant of Allah the most devout. But in reality human beings as individuals had different level of skills, time and opportunities. Therefore, in Islam various educational systems were developed in order to be able to guide people (society) in accordance with the command of Allah. One of the educational and community-based learning groups and is currently growing and growing is Islamic educational institution called Islamic assembly. This assembly is a non-formal educational institution in Islam. It becomes a religious cultural phenomenon that grows and develops in the Indonesian Muslim community. It functions as da’wa institution that has a strategic role in the development of religious life for the community. Keywords: Strategy, Assembly, Da’wa